Short-term and long-term relationships between gold prices and precious metal (palladium, silver and platinum) and energy (crude oil and gasoline) prices. Issue 1 (1st January 2017) - Eryiğit, Mehmet
Abstract: Throughout history, investors have attempted to determine the future states and prices of instruments that they consider to invest in. Thus, various econometric models have been developed in order to determine the variables influencing the prices of investment instruments, as well as the relationships between such variables. The main aim of the present study was to examine the variables that may be related to gold prices. These variables were divided into two groups: precious metals and energy. According to the results of unit root (or stationary) tests and cointegration tests, a vector autoregression model (VAR) was constructed to reveal the short-term interaction between gold prices and precious metals, and a vector error correction model (VECM) was employed to reveal relationship between gold prices and energy prices. The results of the VAR analysis indicated that gold prices have a short-term correlation with silver prices; platinum prices have a short-term correlation with gold and silver prices; and there is a short-term correlation between silver prices and palladium prices. According to the results of the VECM analysis, gasoline and crude oil prices have no long-term correlations with gold prices, but gold and crude oil prices have a long-term correlation with gasoline prices.